Unveiling and Revealing the Mirror: Mobile Reverberations in Patrick Bokanowski's Animated Films. (July 2019) - Rama, Tamara; Lloret, Carmen
The principal focus of this article is to provide an analysis of some of the most significant works by the independent filmmaker Patrick Bokanowski and the methodology he uses to create those animated films. It addresses Bokanowski's technique of filming on various kinds of reflective surfaces as a strategy for transforming the image through optical deformation and thereby expressing his subjective vision in films and animation. He explores the practical application of creating reverberation as visual echoes, as well as the use of unusual reflections that appear in mirrors and other more unstable reflective surfaces, such as liquid mercury, and the refraction occurring in sculpted lenses, glass or water. The aim of this strategy is the pure expression of subjective experience, with the director using a camera as if it were an entirely free-moving paintbrush that inspires creativity and breaks loose from automatic camera movements. Accordingly, this study examines the dynamic, expressive potential of the language of catoptrics, taking as paradigmatic examples two of Bokanowski's short films: La Plage (1992) and Au bord du lac (1994). The authors' analyses of these films are aimed at demonstrating how the artist manages to bring about qualitative, transformative changes of forms and space by reflecting images on mirrors, ripples in mercury and movements of water, and by combining these elements. The system developed by Bokanowski successfully transports us to an ever-changing, poetic universe and breaks new ground in the field of animation.